Bond Behavior of Sand-Coated GFRP Rebar Embedded in Concrete - Sakcali, Gokhan B.; Sagiroglu, Serkan; Yuksel, Isa (Springer International Publishing Ag, 2024)
Bond between rebar and the surrounding concrete is a vital property for the earthquake resistant reinforced concrete (RC) structures. It is required to provide sufficient force transfer between the concrete and rebars for the RC elements to exhibit composite behavior. In this study, it is aimed to examine the bond behavior of the sand-coated GFRP rebar embedded in the concrete. In this context, beam test specimens with three different embedment lengths were prepared in laboratory environment. The behavior of the specimens are investigated comparatively by utilizing the load-displacement relationships, the slippage of the rebar through the concrete, crack propagations, diagonal crack angles, failure modes, bond strength. As a result of the investigations, it was determined that the failure mode changed and accordingly load bearing capacity of the samples increased as the embedment length of the rebars increased. In addition, two different approaches were used to determine the bond stress and the results are discussed comparatively.
International Congress on Advanced Earthquake Resistant Structures (AERS) -- APR 26-28, 2023 -- Baku, AZERBAIJAN
Keywords: Bond; Embedment Length; GFRP; Sand-coated; Slippage